Ambidextrous Leadership On Innovation Performance : The Mediating Role of Employee Creativity At PT Pertamina Patra Niaga Jatimbalinus - Yudha Pratama, Tegar; Kistyanto, Anang (Profesional Muda Cendekia Publishing, 2024)
Research Aims: This study aims to test and analyze the effect of ambidextrous leadership on innovation performance with employee creativity as an intervening variable. Design/methodology/approach: This research uses a quantitative approach involving 48 employees at PT Pertamina Patra Niaga Jatimbalinus Retail Function SBM Lamongan Gresik. The sampling technique used a saturated sample of 48 respondents. The statistical analysis used in this research is SEM PLS with the help of SmartPLS 3.2.9 software. Research Findings: The findings of this study indicate that ambidextrous leadership has no significant effect on innovation performance. Ambidextrous leadership has a significant positive effect on employee creativity. Employee creativity has a significant positive effect on innovation performance. Employee creativity in this study can mediate the influence of ambidextrous leadership and innovation performance. Theoretical Contribution/Originality: This research provides new insights into ambidextrous leadership on innovation performance through employee creativity. Keywords: Ambidextrous leadership, innovation performance, employee creativity